Alpha Amylase Inhibitory Potential and Mode of Inhibition of Oils from Allium sativum (Garlic) and Allium cepa (Onion). (October 2020) - Ahmed, Maryam Usman; Ibrahim, Adamu; Dahiru, Noseh Janyo; Mohammed, Hauwa'u Shuaibu
Background: Alpha amylase inhibitors are used in the treatment of type II diabetes mellitus. Allium sativum and Allium cepa, widely consumed as spices have several medicinal uses which include their traditional use in the management of diabetes. This study was conducted to investigate the alpha amylase inhibitory potential and mode of inhibition of A. sativum and A. cepa oils. Method: Oil was extracted from dried bulb of A. sativum and A. cepa by Soxhlet extraction. The α-amylase inhibitory potential of the 2 oils were evaluated. The mode of inhibition of the oils were determined from the lineweaver-burk plot and the kinetic parameters obtained from the lineweaver – burk plot. Result: A. sativum oil had 58.13 ± 1.09 and 69.8 ± 1.11 percent inhibition at 5.0 and 7.0% concentrations respectively while A. cepa oil had 55.45 ± 1.35, 59.73 ± 1.11 and 65.21 ± 1.11 percent inhibition at 5.0, 7.5 and 10% concentrations respectively. The IC50 values for A. sativum oil, A. cepa oil and acarbose were 3.0 ± 0.02%, 4.4 ± 0.03% and 14.1 ± 0.09% respectively. The lineweaver – burk plot showed that the Vmax of the 2 oils did not change when compared with that of the no inhibitor (no oil) but the Km increased. Conclusion: These findings indicate that A. sativum and A. cepa oils are competitive inhibitors of α- amylase and can both be used in the treatment of type II diabetes mellitus. A. sativum oil is a better inhibitor than A. cepa oil.